2021
DOI: 10.3390/ijerph18105224
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Changes in Physical Self-Concept through Participation in Exercise on Changes in Self-Esteem and Mental Well-Being

Abstract: The aim of the present study was to examine the impact of the changes in physical self-concept induced by exercise participation on the changes in global self-esteem and mental well-being using a structural model analysis. A total of 189 university students in Seoul, Korea, participated in the present study for two waves. The participants responded through a survey measuring physical self-concept, self-esteem, and mental well-being before and after a six-week exercise course. Regression analysis was used to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
1
17
0
2
Order By: Relevance
“…Physical exercise is also a positive way to cope with stress and negative life events, showing a buffering effect and decreasing perceived stress [ 17 , 46 ]. Relevant studies have also provided evidence from different perspectives: physical exercise is negatively related to the negative indicators of social adaptation (e.g., depression, anxiety, and suicide) [ 1 , 2 , 47 ] and positively related to positive indicators (e.g., positive self-conception, psychological capital, and good quality of life) [ 2 , 11 , 48 ]. From the opposite perspective, a lack of necessary physical exercise, such as sedentary behavior and excessive screen time, negatively influences individuals’ health and adaptation, being linked to obesity and overweight, depression, low quality of life, and low self-esteem [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physical exercise is also a positive way to cope with stress and negative life events, showing a buffering effect and decreasing perceived stress [ 17 , 46 ]. Relevant studies have also provided evidence from different perspectives: physical exercise is negatively related to the negative indicators of social adaptation (e.g., depression, anxiety, and suicide) [ 1 , 2 , 47 ] and positively related to positive indicators (e.g., positive self-conception, psychological capital, and good quality of life) [ 2 , 11 , 48 ]. From the opposite perspective, a lack of necessary physical exercise, such as sedentary behavior and excessive screen time, negatively influences individuals’ health and adaptation, being linked to obesity and overweight, depression, low quality of life, and low self-esteem [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…One’s physical self-concept is an important mediator in physical activity, as well as a valuable outcome in itself [ 85 ]. We assessed three subscales of the PSDQ related to self-described endurance, coordination and strength competence.…”
Section: Discussionmentioning
confidence: 99%
“…Conde-Pipó and colleagues found that practicing sport activities for more than 150 min/week was associated with higher scores of physical self-concept in middle-aged and older adults [ 88 ]. Other studies with young adults have shown that changes in physical self-concept through participating in physical activity can lead to improvements in well-being [ 85 , 89 , 90 ]. Presumably, we might have induced similar effects by our study.…”
Section: Discussionmentioning
confidence: 99%
“…11 The effects of exercise participation on physical self-concept have also been found to positively influence mental well-being, and in turn, influence the changes in mental well-being via the improvement of selfesteem. 12 Furthermore, higher levels of physical exercise have been observed to prompt a higher score of subjective well-being over that of low-level exercise. 13 Reasons as to why this may be stem from previously established theories, such as Maslow's Hierarchy of Needs, in which self-esteem plays a significant role as a basic human motivation, as individuals require both appreciation and inner self-respect to build self-esteem and fulfill the requirements to achieve self-actualization.…”
Section: Self-esteem and Physical Exercisementioning
confidence: 99%